Comparison of sectional and strut-and-tie methods for design of pile caps - Geevar, Indu; Majeed, Aysha Zeneeb; Balakrishnan, Bijily (Journal of Structural Engineering, 2024)
Pile caps are deep members provided under the column to safely transmit the loads to the piles beneath. These members can be classified as disturbed regions, due to their low shear span-to-depth (a/d) ratios and traditional sectional methods of design are not valid. These members are popularly designed using the strut-and-tie method. The Indian standards do not have recommendations for strut-and-tie based design and designers usually adopt the sectional method of design considering flexure, shear (one-way and punching), and bearing strengths. The study attempts to compare the strength estimation of pile caps using sectional method in IS 456 and the strut-and-tie method as in ACI 318. The strut-and- tie method predicted about 1.8 times more strength than sectional method for pile caps with shear span-to-depth (a/d) ratios less than 0.9. For a/d > 1.0, the difference in strength prediction is not very significant. Previous studies have shown that the sectional method can lead to unsafe design. Hence, the study strongly recommends strut-and-tie method of design especially for deep pile caps with a/d < 1.